METHODOLOGICAL FOUNDATIONS OF A DIFFERENTIAL APPROACH IN DEVELOPING DIALOGIC SPEECH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article is devoted to the methodological foundations of a differential approach in developing dialogic speech within the framework of English language education. The article is based on concrete facts and written using an analysis of relevant online sources and foreign scientific literature. The study has a scientific-theoretical character, highlighting the importance of developing dialogic speech and the necessity of organizing the educational process with consideration of students’ individual characteristics. Each idea is supported by reliable sources, and the views of scholars and educators are presented with appropriate references (web links). The article demonstrates the essence of the differential approach and methods of applying it in teaching practice by examining the experience of developed countries, while also discussing its expected outcomes and practical significance. In the conclusion, it is emphasized that applying a differential approach can significantly improve students’ dialogic speaking skills, and recommendations are provided for effectively implementing this approach in English language lessons.